LAW ENFORCEMENT AS AN OBLIGATION TO INFORMATION ON AMENDING REIMBURSEMENT LIST - Qendro Gentiana; Malaj Ledjan; Hoti Ela (European Scientific Journal, ESJ, 2013)
﻿Reimbursable drugs list is built on the principle of essential medicines lists. To avoid the negative effects of the pharmaceutical market and help doctors in drug treatment patients Experts Committee of WHO in 1977 has drawn Listen model of essential drugs. The concept of essential medicines is unanimously accepted by the World Health Assembly on, and the list of these medicines was adopted by 120 countries in the world beats. This list is constantly revised and improved several times over the years.Purpose: The evidences of the violation of the law for informing pharmaceutical service as a legal right of pharmacists and as a liability for HII in the case of the approval of the reimbursement list for the coming year.Method: In the study were required reimbursement lists for the period 2007 - 2011 and the price difference for the 10 drugs for this period. Reimbursement lists were analyzed for some of its elements: a. number of new drugs that enter the list and the number of drugs are removed for the period of mare we study, b. change of prices of 10 drugs that have the greatest consumption, c. I change the order that alternatives to these drugs that were taken in the study, d. difference in the price belonging to the patient pay for the same bar.Result and Conclusions: In the end, the conclusion was reached that the entry into force and the beginning of implementation of the reimbursement list in different months of the year without prior notice of changes that were made has caused damage to ALL pharmacies as a result of the stock created drugs that had changed the order of the alternatives. Do not implement the law in relation to preliminary information pharmacists is put before a fait accompli by not leaving any opportunity to reduce stock or to obtain supplies of the drugs that enter the list for the first time or you spend the first alternative .